Vegetius : Epitome of military science - Vegetius, 383-450; Milner, N. P. (Liverpool : Liverpool University Press, 1996)
The only Latin art of war to survive, Vegetius’ Epitome was for long a part of the medieval prince’s military education. The core of his proposals, the maintenance of a professional standing army, was revolutionary for medieval Europe, while his theory of deterrence through strength remains the foundation of modern Western defence policy.
Údaje o elektronické reprodukci převzaty ze SUDOC
Elektronická reprodukce.
Keywords: vojenství -- starověký Řím; military science -- ancient Rome; komentovaná vydání; pojednání; e-knihy online; annotated editions; essays; e-books online